Passive control of sonic flow from converging nozzle with D-shaped rib - Makwana, Mayur Bharatbhai; Bellary, Sayed Ahmed Imran; Khan, Sher Afghan; Aabid, Abdul; Baig, Muneer (Elsevier, 2025)
The abrupt expansion at the blunt base of projectiles, rockets, missiles, and other similar objects is a common phenomenon. The abrupt increase in the base area and the pressure in the separated region cause flow separation and reattachment The recirculation area is at a lower pressure than the surrounding atmospheric pressure. The separation at the blunt base will result in low pressure, resulting in a considerable amount of base drag. In this work, the base pressure, which is lower than the ambient pressure, leading to base drag, is controlled by a passive control method, such as a d-shaped rib. The duct diameter is 25 mm, and its length-to-diameter (L/D) ratio is 6. Ribs of heights ranging from 1 mm to 3 mm were utilized to control the base pressure when located at L/D = 0.5, 1.0, 1.5, 2, and 3. When the rib was located at L/D = 1, the base pressure values for a 3 mm rib height increased considerably. Ribs with smaller heights are more vulnerable to changes in rib placements, as the reattachment point lies between L/D = 2 and 3D. This results in slight variations in the base pressure ratios at other locations. According to the study, 2 mm ribs are the optimum option if the mission requires equating the base pressure to ambient atmospheric pressure. If the mission requires a fifty percent enhancement in base pressure, then even a 1 mm rib is sufficient. The 3 mm rib is the optimal option if the mission requirements require significantly increasing the base pressure.